Utilization of Coal Ash as an Ameliorant to Enhance Growth and Nutrient Availability for Chili Plants (Capsicum annuum L.) on Peat Soil - Farrah Fadhillah Hanum; Budi Setya Wardhana; Imran; Annisa Vada Febriani (Indonesian Journal of Chemical Engineering, 2024)
Peat soil has limitations in nutrient content and low pH, thus requiring improvement efforts to support optimal plant growth.This study aims to examine the effect of adding coal ash (fly ash and bottom ash) on the growth of chili plants in peat soil media.The research design uses a combination of peat soil, manure, and coal ash from the power plant, which are tested under several treatments.The main parameters observed were plant height and nutrient analysis in the growing medium.The results show that the combination of peat soil, manure, and bottom ash from PLTU 2 (GA-B2B) produced the highest plant growth (26.3 cm).The addition of coal ash increases the CaO content in the growing medium, which plays a role in improving the chemical properties of the soil.However, nitrogen levels tend to decrease with the increase in coal ash dosage.Thus, coal ash has the potential to act as an ameliorant to improve the productivity of peat soil, especially when combined with organic fertilizers.